Interpretation of Tabarruj According to M. Quraish Shihab and Its Relevance to the Phenomenon of Self-Expression on Social Media - Febriani Harahap; Salahuddin Harahap (Fakultas Ushuluddin dan Pemikiran Islam Universitas Islam Negeri Raden Fatah Palembang, 2025)
It is undeniable that the frequency of social media access by individuals, especially women, has a significant impact on the social aspects of their lives, particularly in terms of dress and behavior. This is because social media provides individuals with the opportunity to interact with one another without the constraints of time or location. This study aims to explore the understanding and concept of tabarruj according to M. Quraish Shihab's Tafsir al-Mishbah and its relevance to self-expression on social media. This study was conducted using qualitative methods and employed a library research approach along with descriptive-analytical data analysis. The findings of this study indicate that M. Quraish Shihab defines tabarruj as the attitude or behavior of a woman who displays her jewelry and attractive body parts to men who are not mahram, such as showing her chest and neck area, or wearing a headscarf but allowing it to hang down and be open. According to Quraish Shihab, dressing in modern fashion is similar to the clothing worn during the Jahiliyyah period. This interpretation is relevant to women who express themselves through photos or videos posted on social media, which often show parts of the body that, in Islam, should be covered or concealed from the view of non-mahram men. Dressing in a way that exposes the body or adopting a seductive style, even through a screen, can be seen as a form of contemporary tabarruj—a repetition of old patterns in new forms, according to Quraish Shihab’s interpretation.